(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Over 15% of the adult population worldwide may have diabetes mellitus (DM) by 2030, according to predictions from the World Health Organization. SGLT-2 inhibitor is also called gliflozin or flozin, a class of drugs responsible for inhibiting sodium-glucose transport in the nephron (the effective unit of the order), as opposed to an SGLT-1 inhibitor that inhibits sodium-glucose transport in the intestinal mucosa. In people with “type 2 diabetes”, this threshold may rise and the expression of SGLT2 proteins may be constrained, leading to an unfavourable reaction that exacerbates hyperglycemia. For the treatment of “type 2 diabetes”, “SGLT2 inhibitors” are the most recent family of oral hypoglycemic medications to receive approval.